MYTHS OR MEMORIES - Manou, Prodromos (Design/Arts/Culture, 2023)
In the old times, not so old and distant as we think now, the elders also known as ‘the moonstruck’ would gather after a long day at work around a fire, a hearth, and as they removed the weariness of the whole day, they would invite the younger members of the family and would share their memories. Stories of their past, stories they heard of or seen with their own eyes, stories they witnessed and stories they only listened to. Stories so old, from memories faded, forgotten, narratives of incidents changed, that connect with events leading to legends, and folk tales. Tales born from tradition and memory. A very old memory, with a plot easy to understand and usually local - a place near the place of those storytellers. Those entertainers of the not so far away world, would produce images in the minds of their audience, colours and forms as they were responsible for keeping that legend and memory alive. The result of that storytelling around the fire was thousands of images. Then the images would turn to words from that young audience that would grow older and become those elder near the fireplace. It was their time to disseminate the images in the heads of the next generation, and keep those memories alive.